PRESIDENTS WHO CONTRIBUTED GREATLY TO THE DEVELOPMENT OF THE UNITED STATES - Komilova Diyora Tohirjon qizi; Botirova Hakima (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: The main purpose of this given article is that to inform about the presidents of the United States of America and their great contributions to the country's development, including the reforms they have made during their work for the development of their economy and politics as well as their achievements in the field.